The Meningo-Orbital Band: Microsurgical Anatomy and Surgical Detachment of the Membranous Structures through a Frontotemporal Craniotomy with Removal of the Anterior Clinoid Process - Fukuda, Hitoshi; Evins, Alexander I.; Burrell, Justin C.; Iwasaki, Koichi; Stieg, Philip E.; Bernardo, Antonio (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective To describe the microanatomy of the meningo-orbital band (MOB) and its associated membranes, and propose a stepwise method for their detachment while minimizing potential complications.Design Cadaveric and prospective clinical.Setting Microneurosurgery Skull Base Laboratory, Weill Cornell Medical College (New York, NY) and Shiroyama Hospital (Osaka, Japan).Participants Five preserved cadaveric heads (10 sides) and five patients requiring surgical detachment of the MOB in 2012.Results MOB detachment and subsequent extradural anterior clinoidectomies were successfully performed on five clinical cases. Detachment of the MOB was accomplished using a four-step dissection based on the structure's detailed microanatomy and included (1) partial removal of the lateral wall of the superior orbital fissure, (2) incising of the lateral periosteal dura of the superior orbital fissure, (3) peeling off the dura propria of the temporal lobe from the inner cavernous membrane, and (4) fully detaching the exposed MOB from the periorbita.Conclusion Understanding the complex microanatomy of these structures enabled a safe and effective stepwise detachment of the MOB. We recommend that surgeons possess sufficient anatomical knowledge before surgically manipulating this structure.
Keywords: meningo-orbital band; superior orbital fissure; microsurgical anatomy; membranous structure; anterior clinoidectomy